HEPATOPROTECTIVE EFFECT OF A 70% ETHANOL EXTRACT OF GOD'S CROWN FRUIT (PHALERIA MACROCARPA) AGAINST PARACETAMOL HEPATOTOXICITY IN SWISS WEBSTER MICE - Tejo Jayadi (Berkala Ilmiah Kedokteran Duta Wacana, 2019)
Background: The god’s crown fruits have properties as antioxidants and anti-inflammatory. Toxic doses of paracetamol can injure the liver through toxic metabolite bonds with cytoplasmic proteins that cause free radicals to form. The aim of this research is to know the effect of the crown of gods extracts on paracetamol hepatotoxicity. Method: A total of 30 of Webster swiss mice with a weight of ± 20 grams, age 3 months were randomly assigned to five groups, negative control, positive control, treatment 1,2 and 3. A 70% ethanol extract of god’s crown fruit given in doses 60mg, 120mg and 240mg per kgBB mice. The extract was administered for 14 days in the treatment groups, then on day 15 paracetamol ware administered in a given dose 300mg/kgBB for 1 day for the positive control group and treatment groups. On day 16, the serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were examined from the orbital sinuses and animals terminated liver tissues taken and immediately fixed in 10% buffer formalin for histological examination. Results and Discussion: The 70% ethanol extract of the god’s crown fruits decreased blood serum levels of AST and ALT, and these results were supported by histopathologic scores of the liver in which histopathologic scores were improved with the increasing doses (p < 0.05). The secondary metabolite contents of the god’s crown fruit extract served as an antioxidant and anti-inflammatory, protecting hepatic injury from the toxic metabolite of paracetamol. Conclusion: A 70% ethanol extract of god’s crown fruit (Phaleria macrocarpa) have hepatoprotective properties that effectively prevent hepatic injury due to paracetamol toxic dose.